Singing bio acoustic profile of Cicadidae around the enviroment of Mathematics and Natural Sciences Faculty Yogyakarta state University - Hidayati, Sukarni; Subiantoro, Agung W. (Jurnal Sains Dasar, 2014)
This research is done to identify and describe the singing bio acoustic profile of Cicadidae in the environment of Mathematics and Natural Sciences, Yogyakarta State University. This research is a descriptive research through naturalistic observation. The research sample is determine using sampling scan technique for sound which has a highest trending sound intensity on three spots or observation area. The research variables consist of emergence time and Cicadidae singing bio acoustic characteristic. The research instrument used is the Cicadidae singing (sound) audio recorder to obtain Cicadidae singing recording and also the emergence time interval, and bio acoustic (audio) sound analysis software to analyze physical-digitally the characteristic of Cicadidae singing bio acoustic. The data analysis of Cicadidae singing bio acoustic is done descriptively through the analysis results of spectrogram and oscillogram description to show the Cicadidae singing audio characteristic pattern.   Key words: bio acoustic proifle, singing, Cicadidae